2016
DOI: 10.14718/acp.2016.19.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de las diferencias de género en las estrategias de afrontamiento del dolor lumbar

Abstract: ResumenEl dolor lumbar puede ser visto como un gran problema de salud pública. Las diferencias de género son importantes factores que influyen en los síntomas y en las respuestas del comportamiento. El objetivo de este estudio fue investigar las diferencias de género en los comportamientos de dolor y en el manejo del dolor lumbar crónico. La muestra estuvo conformada por 158 participantes (66,5% mujeres), con edades entre los 30 y 88 años que fueron diagnosticados con artrosis lumbar. Los instrumentos utilizad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
3
3
0
1
Order By: Relevance
“…In the present study, CLBP was found to have a major mental health impact, as in other studies [21]. Seven out of ten people referred to having mental health disorders, which was significantly higher in women, with results that were similar to those in Valdés et al [58] (76.73%).…”
Section: General Characteristics Of Participants With Clbpsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, CLBP was found to have a major mental health impact, as in other studies [21]. Seven out of ten people referred to having mental health disorders, which was significantly higher in women, with results that were similar to those in Valdés et al [58] (76.73%).…”
Section: General Characteristics Of Participants With Clbpsupporting
confidence: 89%
“…On the other hand, the constant presence of negative emotions [17], maladaptive coping strategies, catastrophism [18], somatisation, insomnia, depressive mood, widespread pain syndromes, central hypersensitivity syndromes and personality changes are significant predictive variables of worse adaptation to pain and worse perceived health and health [19] at all ages [20], but to a lesser extent in men [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some factors can influence the conduct and effectiveness of the physical therapists, among which we can highlight the difference between genders and the time since graduation. A study published in 2014, which analyzed the views of men and women on low back pain, identified that women have an emotional focus on the individual, while men have a physical focus, In this way, these different views directly influence the individual way in which the professional will carry out their duties [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…De forma coadyuvante con todo lo demás, en la cultura popular, existe el estereotipo de las mujeres como el sexo más emocional (Sánchez Núñez et al, 2008) y la percepción de que las mujeres tienden a centrarse en los aspectos emocionales del dolor (Zavarize & Wechsler, 2016), son más sensibles a los acontecimientos de la vida diaria que generan dolor (de tipo psicológico y social), ya sea por motivos fisiológicos (cambios hormonales) o por motivos culturales y de socialización (educación y roles de género) (Sánchez Aragon et al, 2008), y se asocia esta "sensibilidad" con un umbral del dolor más bajo y al mismo tiempo con una mayor resistencia, es decir, les "duele más" pero "lo resisten mejor" (Biedma Velázquez et al, 2019).…”
Section: **** 1 Introducciónunclassified